Ländliche Entwicklung in Sri Lanka - Knall, Bruno; Wagner, Norbert (Internationales Asien-Forum, 1982)
Since independence rural development in Sri Lanka has concentrated on the Rural Development Societies (RDS). This voluntary, non-statutory villagelevel organization was supposed to coordinate all development measures and to initiate a self-sustaining development process at the village level. Dominance by a few leaders, political influences, lack of own resources, dependence on subsidies from the district-level, little participation in the decision making process by the majority of the rural people, and concentration on traditional community development thinking are the main reasons why the RDS-movement has been of only marginal importance to rural life in Sri Lanka. A new approach in rural development, the Change Agents Programme, focuses on the participation of the rural poor and on the raising of their incomes by breaking exploitive dependencies on middlemen. This approach indicates one possible direction in the necessary re-orientation of the rural development policy and, in combination with the RDS-movement, it might be of great importance for the future rural development of Sri Lanka.
Elektronische Reproduktion der Druckausgabe